Reproductive parameters of vicuñas (Vicugna vicugna) in the Cusco region, Peru - Pacheco, Joel Iván (2019)
The aim of this study was to determine some reproductive parameters (gestation rate, number of young, age distribution and reproductive age) of female vicuñas in two management systems: wild and captivity, in the Cusco Region, Peru. The capture of the animals ("Chaccus") were carried out between May and August 2017. The pregnancy was determined by transrectal ultrasound in 143 females, the presence of offspring by observing functional udder in the females, the age distribution and reproductive age by means of the records of capture and observation of the dentition. The percentage of gestation was of 74.6 and 79.4% for the wild and captivity systems, respectively. In the juvenile population were pregnant 29.9 and 4.4% in the wild and in captivity, respectively. The number of young animals in the wild was 36% and in captivity 53%. The proportion of young vicuñas was similar in both management systems, of juveniles was 20.1% in captivity and 3.3% in the wild and 84.9 and 66.3% in adults in captivity and in the wild, respectively.